Árni Magnússon, an early-modern collector of medieval manuscripts - Már Jónsson (Tabularia)
The article provides an overview of the life and work of the Icelandic scholar Árni Magnússon (1663-1730), collector of manuscripts and professor of history at the University of Copenhagen. He started collecting Icelandic manuscripts as a young man and his collection is now the basis for all research on Medieval Iceland. It also contains Norwegian and Danish medieval manuscripts, as well as more recent Icelandic ones.